Marine ice formation in a suture zone on the Larsen C Ice Shelf and its influence on ice shelf dynamics. Issue 3 (30th August 2013) - Jansen, Daniela; Luckman, Adrian; Kulessa, Bernd; Holland, Paul R.; King, Edward C.
Abstract [1] Antarctic ice shelves are fed primarily by the glaciers flowing into them. Downstream of promontories separating these glaciers, supercooled water can rise and freeze into suture zones, leading to the accretion of marine ice. Marine ice bodies have been found in several Antarctic ice shelves, but little is known about their detailed geometry, rate of accretion, or influence on ice dynamics. In this study, we investigate marine ice in a suture zone downstream of the Joerg Peninsula in the southern part of the Larsen C Ice Shelf, Antarctic Peninsula. We present ground penetrating radar data from which we infer the base of the meteoric ice and, in combination with GPS data and assuming hydrostatic equilibrium, estimate marine ice thickness within a suture zone. We show that the Joerg Peninsula suture zone contains marine ice layer, which is increasing in thickness along flow from ~140 m to 180 m over 20 km, implying an average basal accretion rate of ~0.5 m a−1 in our study area. We examined the impact of this inferred marine ice on ice shelf dynamics by modeling the suture zone within an ice flow model. The results, which replicate observed surface velocities and strain rates, show that the warmer and thus softer ice of the suture zone serves to channel shear deformation. This enables decoupling of neighboring flow units with different flow velocities, while maintaining the structural integrity of the ice shelf.